Chromatin dynamics of plant telomeres and ribosomal genes - Dvořáčková, Martina; Fojtová, Miloslava; Fajkus, Jiří (The Plant journal, 2015)
Telomeres and genes encoding 45S ribosomal RNA (rDNA) are frequently located adjacent to each other on eukaryotic chromosomes. Although their primary roles are different, they show striking similarities with respect to their features and additional functions. Both genome domains have remarkably dynamic chromatin structures. Both are hypersensitive to dysfunctional histone chaperones, responding at the genomic and epigenomic levels. Both generate non-coding transcripts that, in addition to their epigenetic roles, may induce gross chromosomal rearrangements. Both give rise to chromosomal fragile sites, as their replication is intrinsically problematic. However, at the same time, both are essential for maintenance of genomic stability and integrity. Here we discuss the structural and functional inter-connectivity of telomeres and rDNA, with a focus on recent results obtained in plants.
Keywords: histony; Plants; telomere; Arabidopsis thaliana; epigenetics; nestabilita genomu; epigeneze genetická; ribozomální DNA; Genomic Instability; rDNA; chromatin; rostliny; DNA rostlinná; Chromatin; DNA, Plant; Nicotiana tabacum; telomery; replikace DNA; DNA Replication; Histones; DNA, Ribosomal; Telomere; Epigenesis, Genetic